Rat aquaporin-5 4.3-kb 5′-flanking region differentially regulates expression in salivary gland and lung in vivo - Zhou, Beiyun (American Physiological Society, 2008)
We previously cloned a 4.3-kb genomic fragment encompassing 5′-flanking regulatory elements of rat aquaporin-5 (Aqp5) that demonstrated preferential transcriptional activity in lung and salivary cells in vitro. To investigate the ability of Aqp5 regulatory elements to direct transgene expression in vivo, transgenic (TG) mice and rats were generated in which the 4.3-kb Aqp5 fragment directed the expression of enhanced green fluorescent protein (EGFP). RT-PCR revealed relative promoter specificity for the lung and salivary glands in TG mice. Immunofluorescence microscopy showed strong EGFP expression in salivary acinar cells but not in lung type I (AT1) cells, both known sites of endogenous AQP5 expression. Similar results were obtained in TG rats generated by lentiviral transgenesis. EGFP mRNA was detected in both salivary glands and lung. Robust EGFP fluorescence was observed in frozen sections of the rat salivary gland but not in the lung or other tested tissues. The percentage of EGFP-positive acinar cells was increased in parotid and submandibular glands of TG rats receiving a chronic injection of the β-adrenergic receptor agonist isoproterenol. EGFP-positive cells in the lung that were also reactive with the AT1-cell specific monoclonal antibody VIIIB2 were identified by flow cytometry. These findings demonstrate that the 4.3-kb Aqp5 promoter/enhancer directs strong cell-specific transgene expression in salivary gland and low-level AT1 cell-specific expression in the lung. While these Aqp5 regulatory elements should be useful for functional studies in salivary glands, additional upstream or intronic cis-active elements are likely required for robust expression in the lung.